What are the best treatments for actinic keratosis?. Issue 5 (May 2017) - Manek, Megha; Bhingradia, Rupal B.; Ros, Oliana
Abstract : EVIDENCE‐BASED ANSWER : For complete clearance of lesions, 5‐fluorouracil, diclofenac, imiquimod, and ingenol mebutate are more effective than placebo. Of these agents, 5‐fluorouracil is the most effective. For individual lesions, photodynamic therapy is superior to cryotherapy (SOR: A, meta‐analysis of RCTs, network analysis of RCTs).